Antiphospholipid Antibody Profile in HIV/AIDS Patients - Pandjaitan, Inolyn; Sukmana, Nanang; Effendy, Shufrie (UI Scholars Hub, 2017)
Introduction. Through the process of molecular mimicry, human immunodeficiency virus (HIV) infection can increase the concentration of antiphospholipid antibody (APA) which has possible association with thrombosis. The molecular mimicry in this HIV/AIDS patients is influenced by several factors, such as immunocompromised condition, the use of antitretroviral (ARV) therapy, hepatitis B and C coinfection, use of other drugs, and history of intravenous drug user (IDU). We conducted this study to determine the profile and prevalence of antiphospholipid antibody in patients with HIV/ AIDS in Dr. Cipto Mangunkusumo General Hospital. Further, we explored the relationship between APA in HIV/AIDS patients with the factors mentioned before. Methods. This cross sectional study was done on HIV/AIDS outpatient at AIDS Working Group Clinic at Dr. Cipto Mangunkusumo General Hospital. We assessed the patients by history taking and measured their level of antibody anticardiolipin (ACA) dan Anti β2 glycoprotein I (anti-β2 GP1). Subjects were selected using simple random sampling. Descriptive data regarding the characteristics of the subjects and the proportions of APA were presented in numbers and percentages. The bivariate analysis between APA with the history of injecting drug use, the absolute CD4 lymphocyte count, antiretroviral therapy, and chronic hepatitis coinfection was performed using Chi-Square test and Fisher test. Results. APA examination results showed 27 (29,3%) patients were positive for ACA IgM, 77 (83,7%) patients were positive for ACA IgG, 61 (66,3%) patients were positive for anti β2 GP1 IgM, and 7 (7,6%) pateints were positive for anti β2 GP1 IgG. There is significant association between APA and the history of intravenous drug user (IDU) and ARV therapy. No association was observed between CD4 lymphocyte count and hepatitis coinfection with prevalence of APA in patients with HIV/AIDS patient. Conclusion. Proportion of anticardiolipin antibody IgG is higher than IgM (83,7% vs 29,3%), while the proportion of anti-β2 GP1 IgM is higher than IgG (66,3% vs 7,6%).